1994
DOI: 10.1254/jjp.66.421
|View full text |Cite
|
Sign up to set email alerts
|

Aconitine-Induced Increase and Decrease of Acetylcholine Release in the Mouse Phrenic Nerve-Hemidiaphragm Muscle Preparation

Abstract: ABSTRACT-The effect of aconitine on acetylcholine (ACh) release from motor nerve terminals in the mouse phrenic nerve-diaphragm muscle preparation was studied by a radioisotope method. Both electrical stimulation-evoked release and spontaneous release of 3H-ACh from the preparation preloaded with 3H choline were measured. The change in the muscle tension was simultaneously recorded in the same prepara tion. Aconitine (0.1 ttM) increased electrically evoked 3H-ACh release, while at higher concentrations (0.3 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The present study also demonstrated that aconitine increases the frequency of both spontaneous GABAergic IPSCs and glutamatergic EPSCs in rat VMH neurons. Comparable neurotransmitter release response have been described for the spontaneous acetylcholine release in the mouse (Okazaki et al ., 1994) and rat (Onur et al ., 1995) neuromuscular junctions. Since the mean amplitude of spontaneous IPSCs was not significantly changed (Figure 2), aconitine does not appear to alter the sensitivity of postsynaptic GABA A ‐receptor‐channel complexes to transmitter released from presynaptic nerve terminals.…”
Section: Discussionmentioning
confidence: 58%
“…The present study also demonstrated that aconitine increases the frequency of both spontaneous GABAergic IPSCs and glutamatergic EPSCs in rat VMH neurons. Comparable neurotransmitter release response have been described for the spontaneous acetylcholine release in the mouse (Okazaki et al ., 1994) and rat (Onur et al ., 1995) neuromuscular junctions. Since the mean amplitude of spontaneous IPSCs was not significantly changed (Figure 2), aconitine does not appear to alter the sensitivity of postsynaptic GABA A ‐receptor‐channel complexes to transmitter released from presynaptic nerve terminals.…”
Section: Discussionmentioning
confidence: 58%
“…To investigate the effect of cell depolarization on the CCh (10 μM)-induced [Ca 2+ ]i elevation, the Na + channel openers, veratridine (Son et al, 2004) and aconitine (Okazaki et al, 1994), were applied with 10 μM CCh and the effects were compared with those of 10 μM CCh alone. Veratridine (10 μM) and aconitine (10 μM) significantly augmented the CCh (10 μM)-induced [Ca 2+ ]i elevation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the Na + channels openers result in depolarization of the plasma membrane by inducing Na + invasion (Son et al, 2004;Okazaki et al, 1994), the finding that both the drugs augmented the CCh (10 μM)-induced [Ca 2+ ]i elevation indicated that membrane depolarization caused the Ca 2+ influx by activating the voltage-dependent Ca 2+ channels (Fig. 2).…”
Section: Discussionmentioning
confidence: 96%